2021
DOI: 10.3389/fpsyg.2021.728903
|View full text |Cite
|
Sign up to set email alerts
|

Populated Places and Conspicuous Consumption: High Population Density Cues Predict Consumers’ Luxury-Linked Brand Attitudes

Abstract: Population density has been identified as an ecological factor with considerable behavioral implications. The present research aimed to examine whether the mere perception of more (vs. less) populated places can change consumers’ luxury-linked brand attitudes. To this end, we experimentally manipulated consumers’ perceptions of population density using pictorial exposure to high (vs. low) population density cues. The results revealed a significant interaction between manipulated population density and perceive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 76 publications
0
4
0
Order By: Relevance
“…Conversely, in areas with more regular movements, encounters with others may be more frequent, leading to a perception of higher population density. Moreover, in areas with more irregular movements, individuals may have less predictable spatial relationships with others, which can decrease their perception of population density [47][48][49].…”
Section: Population Density Estimatementioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, in areas with more regular movements, encounters with others may be more frequent, leading to a perception of higher population density. Moreover, in areas with more irregular movements, individuals may have less predictable spatial relationships with others, which can decrease their perception of population density [47][48][49].…”
Section: Population Density Estimatementioning
confidence: 99%
“…In conclusion, we have focused our research study on establishing a robust and quantitative description of population mobility, laying the groundwork for further and more rigorous studies that can connect socio-economic indicators to mobility patterns. An exhaustive explanation of the empirical results goes beyond the purpose of the work, but could lead to an interesting discussion in behavioral and transportation economics to better understand how spatial cognition shapes mobility patterns [47,[61][62][63].…”
Section: Proof the Proposition Is Proved In Appendix Cmentioning
confidence: 99%
“…Conversely, in areas with more regular movements, encounters with others may be more frequent, leading to a perception of higher population density. Moreover, in areas with more irregular movements, individuals may have less predictable spatial relationships with others, which can decrease their perception of population density [61][62][63].…”
Section: Population Density Estimatementioning
confidence: 99%
“…Howarth et al (2020) in a systematic review identified the need for more empirical research to identify whether pharmacists in rural and urban settings may have significant differences in behavior and attitude to practice [8]. This assertion was corroborated by a study situated in densely populated China which showed that consumers in low and highlypopulated areas tend to have a behavioral effect on consumers' attitudes and perceptions of luxury goods [9].…”
Section: Introductionmentioning
confidence: 98%